Crowfunding Audiovisual Productions in Spain: The Case of Verkami - Leibovitz, Talia (Iluminace, 2013)
The English-language study examines the financing of films through online platforms that collect funding for film production from a large number of contributors (crowdfunding), focusing in particular on the motives of donors to the Catalan platform Verkami.
Keywords: Internet and film; financing; sponsorship; film marketing; production; production costs